An approach to optimize manufacturing productivity: A pilot study on labor intensive industries - M. I., Shahidul; S. T., Syed Shazali; M.J.S., Hashimi (2010)
A pilot study was conducted on labor intensive industries to measure the impact of intangible resource inputs on manufacturing productivity. Three intangible resource inputs, degree of skills of labor, favorable working environment, R & D knowledge, were used to measure the impact on productivity. Firm’s data of business operations of sample manufacturing industries, have been used for analysis.Study showed, a positive but weak correlation (r<0.5) exists between the inputs of basic skills and productivity, a positive but moderate correlation(r>0.5) exists between inputs of upgraded working environment and productivity.A strong and positive correlation is found (r>0.7) between R & D based inputs and productivity. Additionally, the productivity gain ratio was found significantly good (rp >1.3) for R & D base inputs. Study concludes, expenditure on manufacturing R & D is essentially important to generate knowledge as higher value added input to have higher productivity.